Correlation of Seismicity With Faults in the South Korea Plateau in the East Sea (Japan Sea) and Seismic Hazard Assessment - Kim, Han-Joon; Moon, Seonghoon; Jou, Hyeong-Tae; Kim, Kwang-Hee; Yi, Bo Yeon (Frontiers in Earth Science, 2022)
The South Korea Plateau (SKP) is a structural high at the eastern continental margin of the Korean Peninsula. Earthquakes occur frequently in the SKP although they are not larger than ML 5.0 in magnitude. The SKP is a region of highly rifted continental crust engraved with rifts created during back-arc rifting in the NW Pacific subduction zone that led to the separation of the SW Japan Arc in the Cenozoic. The Bandal, Onnuri, and Okgye Rifts are well-defined rifts in the SKP. Multichannel seismic profiles show that the rifts in the SKP are bounded by large-offset normal faults and their subsided basement is deformed by domino-style faulting. A close spatial correlation is recognized between the epicentral locations of earthquakes with relatively large magnitude and the rift-bounding fault of the Onnuri Rift. The faults in the SKP is interpreted to be reactivated with strike-slip since the Middle Miocene. The maximum expected magnitude of earthquakes (Mmax) computed statistically using the catalog including instrumentally recorded seismicity is ML 5.42. However, Mmax estimated from the catalog including instrumentally recorded seismicity and historical records increases to ML 6.67.